Integrating knowledgments: The rol of taxonomists against other scientific disciplines - Cuezzo, Fabiana del Carmen (2013)
Taxonomy is a part of biology that explores, discovers, represents, names and organizes the life by its process of origin (Ebach et al., 2011). In a society, a taxonomist performs various tasks that pass frequently unnoticed. Basic tasks of a taxonomist include two main: one, more devoted to the scientific community, is to delimit and classify the basic units of biodiversity, the species, and other, open to the rest of the community, is to give a name to this entities and provide tools to facilitate the identification of the species (or other taxon) in form of descriptions, reviews, monographs and taxonomic keys. Then, it is important to recognize that: a) a taxonomist is not a simple “giver of names”, anchored to the past and b) the only interest of his life is not to make lists of species. If the latter were true, every taxonomist could be easily replaced by a machine, as the mythical, but fabulous, bar-code portable lector created to identify species at the ground with only one pass. Research made by taxonomist involve much more than those above mentioned. In the process to describe and represent a new organism or the diversity of life, a taxonomist makes comparisons with other organisms, but not arbitraries, assuming a unity of origin; establishing relationships in function of an objective and concrete value of the shared homologies. The taxonomic classifications have this predictive value, not only by those that include, but also by these that not include in it (Platnick, 2009) and create a theoretical framework within which to develop projects and research. The lack of taxonomist and funding to the development of his work, in the last two decades, was named as “taxonomic impediment”. This “impediment” has, however, several faces, and one of this is to find ways to accelerate the process to describe and delimit the taxonomic units, the species, facing to the community that require this names as base of its own researches. A possible way to solve this impediment is to establish a more close collaboration between researchers in several disciplines, such as ecologists, biogeographers, morphologists, chemists, and taxonomists, between others. If information and specimens are shared is possible to advance faster. Taxonomists share the same basic object of study with several other researchers, but differ in the objective of his studies and in the languages used to face his own research. Thus, an ecologist interested in community studies or diversity, look for the species not as single units but as members of a community and try to build models that explain, for example, the structure of the community, with a more statistical or mathematical thinking. The same community, studied by a biogeographer will be seen from a totally different perspective, interested in the spatial distribution of these species than in the functioning or structure of the community. A taxonomist, however, seek to interpret the affinities between the species in that community and if they share common histories that have led to coexist in the same space. To share experiences from different fields of research can help to accelerate the complex process of knowledge of the planet's biodiversity. But first, we need to learn how to communicate our interest to other researchers in the clearest way possible. An ecologist or biogeographer, for example, needs to learn the “taxonomic language”, spending some time reading reviews or keys, making a fluid dialog with taxonomists, clearly telling which is the purpose and why they need to know the identity of the taxa studied. And the taxonomists need the same to communicate efficiently with their counterparts. If a researcher has no expertise in taxonomy and he or she will need species identification (or at least to corroborate it), and other information that could be given by a taxonomist, they first needs to do some homework before to contact a specialist. It is necessary to remember that the taxonomist need help to help. A first step to help is to provide samples as clean as possible. It is important to separate from the original sample, a sub-sample of well curated specimens, part of which will be send to the taxonomist and the other part will constitute a reference collection that will be really useful for future research. If the material cannot be curated, at least could be sorted as much as possible and labeled. To do the first sort to morphospecies, researchers must take advantage of the multiple resources available in the World Wide Web. In the case of the myrmecological works, there are several data bases that are really useful to provide reliable identifications, at list at generic rank. Excellent examples are: antbase.org (the first impressive base that join a big amount of taxonomical papers catalogued by authors and taxon); antweb.org (images); antcat.org (taxonomic references, an online catalog to ant references), the gap initiative: gap.entclub.org (a list of ant taxonomists and much more), etc. It is important to recognize that a good image alone is not enough to identify correctly a species, but is a really useful tool to provide us a first approach. Try to identify these samples using available keys, it will reduce the labor of the taxonomist. Unfortunately, the automated ID is not always possible today (Gaston, 2004). Spend some time to learn some basic characters used in the group. Some ecologists take courses or send students to learn more about a specific taxonomic group. Hymenopterists has the advantage to have excellent experiences in this kind of courses: Antcourse, Hymcourse, and local versions of those in several countries that deals specifically with local fauna. Establishing a fluid contact with the specialist (in that case a taxonomist), will be another good choice. Usually the taxonomist can provide a lot of information that is not published anywhere and is part of their experience in their daily work, and, if possible, visit local museums or collections to compare your samples with the specimens deposited there. Think to preserve your material for future research, invest time to prepare and deposit vouchers from your ecological study, a practice well implemented between taxonomists, but not always follow by other researchers. And finally, as Gotelli (2004) clearly says: “collaborations between taxonomist and ecologists (or, as I think, other researchers such as biogeographers) will strengthen both research programs”. Collaborative efforts could increase benefit, and contribute to shovel the taxonomic impediment that is evident in our day.